Cleaning solution containing a mixture of polyoxyalkylene nonionic surfactants for cleaning metal surfaces

By combining acid and surfactants with different cloud points in the cleaning solution, the problem of poor cleaning effect at high temperatures is solved, and efficient metal surface cleaning and metal layer adhesion are achieved.

JP7669114B2Active Publication Date: 2025-04-28ATOTECH DEUT GMBH & CO KG
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2019572604
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-07-04
Filing Date
2018-07-04
Publication Date
2025-04-28
Estimated Expiration
2038-07-04

AI Technical Summary

Technical Problem

Existing cleaning solutions are not effective in cleaning metal surfaces at high temperatures and are difficult to maintain high cloud points to ensure effective cleaning.

Method used

Use a cleaning solution containing at least one acid (such as sulfuric acid or methsulfate), a first surfactant (with cloud point ≤25°C) and a second surfactant (with cloud point ≥30°C or ≥45°C).

Benefits of technology

It achieves good wetting and cleaning effects at high temperatures, quickly removes solution residue, low bubble amount, and reduces surface tension, which improves the adhesion of the metal layer on the metal surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669114000033
    Figure 0007669114000033
  • Figure 0007669114000034
    Figure 0007669114000034
  • Figure 0007669114000035
    Figure 0007669114000035
Patent Text Reader

Abstract

1. A cleaning solution for cleaning and / or wetting metal surfaces, the cleaning solution comprising at least one acid, a first surfactant, the first surfactant being an alkyl poly(ethylene glycol-co-propylene glycol) ether having a cloud point of ≦25° C., and a second surfactant selected from the group consisting of: i) an alkyl poly(ethylene glycol-co-propylene glycol) ether having a cloud point of ≧30° C.; ii) an alkyl polyethylene glycol ether having a cloud point of ≧45° C., wherein the cloud point is determined according to the German version of European Standard EN 1890:2006, section 8.2, with the modifications using 10 wt. % HSO as solvent and a surfactant concentration of 1000 mg / L.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THEINVENTION The present invention relates to a cleaning solution for cleaning metal surfaces and to a method of cleaning metal surfaces using said cleaning solution.

[0002] An important prerequisite for successful plating of printed circuit boards (PCBs) is efficient surface pretreatment. During PCB production, the surface is cleaned before the metal layer is deposited on the surface of the PCB. Cleaning ensures that the deposited metal layer adheres better to the surface, resulting in a deposit that is free or nearly free of defects.

[0003] 2. Background of the Invention A large number of cleaning solutions are known from the prior art.

[0004] For example, U.S. Patent Application Publication No. 2008 / 0200360 discloses an aqueous solution for removing ionic contaminants from a surface of a workpiece having a solder mask and a top surface layer, the solution comprising: a) at least one first compound selected from ethanolamine compounds and salts thereof; and b) at least one second compound selected from the group including alcohol-based solvents.

[0005] Cleaning solutions often contain surfactants, and it is desirable for the cleaning solution to exhibit good wetting of surfaces.

[0006] The cloud point of a surfactant refers to the temperature at which the surfactant forms relatively large micelles or even undergoes phase separation, causing the solution to become cloudy. The cleaning properties of the solution are good when the solution is applied at a temperature below or near the cloud point. The cleaning properties are best when the temperature of the solution is slightly higher than the cloud point. To obtain good cleaning results, it is desirable to use a cleaning solution at a high temperature. And it is beneficial if this high temperature is equivalent to or slightly higher than the cloud point. If the cloud point is low, the processing temperature will exceed the cloud point too much, and the solution will lose its effectiveness due to clouding, reducing its cleaning properties. Therefore, it is desirable to have a high cloud point, which is approximately the same as the processing temperature.

[0007] Objective of the invention It is therefore an object of the present invention to provide a cleaning solution which has good cleaning properties, especially at high temperatures.

[0008] It is a further object of the present invention to provide a cleaning solution that has good wetting properties, especially at high temperatures.

[0009] It is a further object of the present invention to provide a cleaning solution that has good cleaning properties and a high cloud point.

[0010] It is a further object of the present invention to provide a cleaning solution that has good wetting properties and a high cloud point.

[0011] Summary of the Invention The solution to this object is achieved by a cleaning solution according to claim 1. Further embodiments are the subject matter of the dependent claims.

[0012] The present invention relates to a cleaning solution for cleaning and / or wetting metal surfaces, said cleaning solution comprising: at least one acid, preferably an inorganic acid and / or methanesulfonic acid, - a first surfactant which is an alkyl poly(ethylene glycol-co-propylene glycol) ether having a cloud point of ≦25° C., preferably ≦23° C.; and - a second surfactant selected from the group consisting of: i) alkyl poly(ethylene glycol-co-propylene glycol) ethers having a cloud point of ≧30° C., preferably ≧35° C., and ii) an alkyl polyethylene glycol ether having a cloud point of ≧45° C., preferably ≧50° C., more preferably ≧55° C., and even more preferably ≧60° C. Including, wherein the cloud point is determined according to the German version of European Standard EN 1890:2006, section 8.2, with the amendments of 10% by weight H2SO4 as solvent and a surfactant concentration of 1000 mg / L.

[0013] The cleaning solutions of the present invention provide good and fast wetting and cleaning, a high cloud point for the solution, good and fast removal of the solution after use, and low foaming. [Brief description of the drawings]

[0014] [Figure 1] The dynamic surface tension of surfactant mixtures of the present invention is shown in comparison to the individual surfactants. [Diagram 2] The dynamic surface tension of surfactant mixtures of the present invention is shown in comparison to the individual surfactants. [Diagram 3] The dynamic surface tension of a surfactant mixture (comparative example) is shown in comparison to the individual surfactants. [Figure 4] 1 shows cleaning results obtained using cleaning solutions of the present invention and comparative cleaning solutions. [Diagram 5] A cross section of a through-hole showing (1) the solder in the through-hole, (2) the base material including glass fibers, (3) the stack of copper layers deposited on the walls of the through-hole, and (4) the copper inner layer.

[0015] Detailed Description of the Invention It has been found that the cleaning solutions of the present invention, in general or in specific embodiments, provide one or more of the following advantages.

[0016] - Good and fast cleaning of metal surfaces. Organic and inorganic contaminants are very well and quickly removed from metal surfaces by the cleaning solution of the present invention. Examples of organic contaminants include organic materials resulting from previous manufacturing steps, such as residual particles of photoresist, fingerprints, glove marks, glove marks resulting from components of the glove's raw material or lubricating grease. Inorganic contaminants can be metal oxides, which are formed on metal surfaces when they are in contact for some time with oxygen, for example from the air. Inorganic contaminants can also result from previous manufacturing steps, such as carbonate residues formed during the development of photoresist.

[0017] Cleaning improves the adhesion of the metal layer deposited on the metal surface and results in a deposit that is free or nearly free of defects.

[0018] - good wetting. Good wetting leads to an effective and uniform cleaning of the surface. If the surface is subsequently rinsed with water, after cleaning the water is distributed more evenly over the surface, improving the wetting of the water, especially in the area of ​​blind microvias (vertical interconnect access) and through-holes. Furthermore, the chemicals used in further processing steps, e.g. the chemicals of the copper deposition bath, can reach the surface better and more uniformly. Furthermore, rapid wetting is obtained, which makes the cleaning solution of the present invention particularly suitable for application in industrial manufacturing processes, e.g. PCBs.

[0019] - High cloud point of the solution, so the cleaning solution can be used effectively at high temperatures.

[0020] - Good and fast removal of the cleaning solution after use. Removal is important because residual surfactants on the metal surface reduce the adhesion of the metal in further processing steps. Furthermore, it is desirable to be able to remove the solution in a short time to improve the speed of the entire process.

[0021] - Low foaming. Foam is a drawback in processing. Firstly, it reduces the solution level, which is a drawback in the cleaning process. Secondly, it has to be removed to avoid drawbacks in subsequent processing steps such as metallization. However, foam removal is time consuming and cumbersome in terms of the consumption of cleaning water.

[0022] Furthermore, it has been surprisingly found that a synergistic effect in wetting, i.e., surface tension, can be achieved in cleaning solutions, where the addition of a combination of the above surfactants results in a mixture with a lower surface tension than would be expected or predicted from the surface tension of the combined surfactants, as will be illustrated in more detail in the accompanying examples.

[0023] The cleaning solution is preferably an aqueous cleaning solution, i.e. based on water as a solvent. Preferably, the balance of the cleaning solution composition is water, which together with the further components amounts to 100% by weight.

[0024] As mentioned above, the cleaning solution for cleaning and / or wetting metal surfaces comprises at least one acid. Preferably, the concentration of the at least one acid is in the range of 1-50% by weight of the cleaning solution of the invention, more preferably 5-30% by weight, even more preferably 5-20% by weight.

[0025] The at least one acid is preferably an inorganic acid and / or methanesulfonic acid. As inorganic acid, sulfuric acid, hydrochloric acid, sulfamic acid (H3NSO3) or phosphoric acid can be used, but sulfuric acid is preferred. The at least one acid in the cleaning solution of the present invention is advantageous because it simultaneously activates the metal surface or prevents the passivation of the metal surface. When a metal surface, such as a copper surface, is exposed to oxygen, for example from air, for a long time, metal oxides, for example CuO, are formed on the metal surface. The metal oxide layer passivates the underlying metal surface. This means that the deposition and adhesion of further metal layers to the metal surface is impaired or prevented. Advantageously, the at least one acid in the cleaning solution of the present invention removes metal oxides and carbonates from the metal surface, while the cleaning solution removes organic contaminants from the metal surface.

[0026] Furthermore, the pH of the cleaning solution for cleaning and / or wetting the metal surface is adjusted to a low pH value by at least one acid. Preferably, the pH value of the cleaning solution of the present invention is less than 2.0, more preferably between 0 and 2.0, even more preferably between 0 and 1.5. Such a low pH value is also advantageous because it prevents the photoresist that may be present on at least a part of the metal surface from being attacked or removed from the metal surface.

[0027] Specific embodiments of the cleaning solutions of the present invention are set forth below. The embodiments may be practiced alone or in any combination. The ratios and range limits disclosed herein may be combined in any combination.

[0028] In one particular embodiment, the weight ratio of the first surfactant to the second surfactant in the cleaning solution is in the range of 1:0.5 to 1:10, preferably 1:1 to 1:8, more preferably 1:2 to 1:6, even more preferably 1:2 to 1:4, and most preferably 1:3 to 1:4.

[0029] In a further embodiment, the concentration of the first surfactant in the cleaning solution is from 50 to 5000 mg / L, preferably from 100 to 1500 mg / L, more preferably from 100 to 1000 mg / L, even more preferably from 150 to 750 mg / L.

[0030] In yet another embodiment, the concentration of the second surfactant in the cleaning solution is 50 to 20,000 mg / L, preferably 100 to 4,000 mg / L, more preferably 300 to 2,800 mg / L, even more preferably 300 to 2,400 mg / L, and most preferably 500 to 2,000 mg / L.

[0031] Preferred embodiments of the first and second surfactants are described below.

[0032] As mentioned above, the first surfactant is an alkyl poly(ethylene glycol-co-propylene glycol) ether. The alkyl group can have 6 to 30 carbon atoms, preferably 6 to 22 carbon atoms, more preferably 8 to 15 carbon atoms. There can be a mixture of molecules in the first surfactant with different alkyl groups. Preferably, the alkyl group is a straight-chain, unbranched alkyl group.

[0033] In a further embodiment, the alkyl group is preferably one or more branched alkyl groups (when different alkyl groups are present).In another embodiment, the alkyl group is mainly composed of one or more branched alkyl groups, which means that unbranched alkyl groups may be present in small amounts.A highly preferred first surfactant comprises or consists of isodecyl poly(ethylene glycol-co-propylene glycol) ether.When the first surfactant comprises isodecyl poly(ethylene glycol-co-propylene glycol) ether, said compound is the main compound, i.e., the first surfactant mainly comprises said compound.

[0034] The poly(ethylene glycol-co-propylene glycol) part of the first surfactant can have a statistical length and weight distribution. Thus, the first surfactant can have a mixture of molecules with different lengths of poly(ethylene glycol-co-propylene glycol) part. As mentioned above, this can be combined with different alkyl groups. Thus, the first surfactant can have different alkyl and poly(ethylene glycol-co-propylene glycol) parts.

[0035] Therefore, the first surfactant is preferably a mixture of molecules with different molecular weights, in other words a statistical distribution of molar weights. Preferably, the first surfactant has a molecular weight in the range of 350 to 950 g / mol. The maximum of the molecular weight distribution curve is preferably 500 to 600 g / mol, more preferably 500 to 560 g / mol.

[0036] The first surfactant is preferably selected from Marlox MO 154 (Sasol Germany GmbH, CAS 68439-51-0), Marlox FK 64 (Sasol Germany GmbH, CAS 68154-97-2), Antarox B12DF (Solvay Solutions Nederland BV, CAS 37311-00-5), Propetal 120, Propetal 105 (CAS 155683-77-5 or CAS 154518-36-2) and Dehypon 2574 (BASF), more preferably selected from Propetal 120 and Propetal 105.

[0037] As mentioned above, the second surfactant is i) an alkyl poly(ethylene glycol-co-propylene glycol) ether, or ii) Alkyl polyethylene glycol ether It may be.

[0038] In surfactants i), the alkyl group preferably has 6 to 22 carbon atoms, more preferably 8 to 18 carbon atoms. The surfactant may contain a mixture of molecules with different alkyl groups. Preferably, the alkyl group is a linear, unbranched alkyl group.

[0039] The poly(ethylene glycol-co-propylene glycol) moieties of surfactant i) may have a statistical length and weight distribution. Thus, surfactant i) may have a mixture of molecules with different lengths of poly(ethylene glycol-co-propylene glycol) moieties. As mentioned above, this can be combined with different alkyl groups. Thus, surfactant i) may differ in both the alkyl and poly(ethylene glycol-co-propylene glycol) moieties.

[0040] Thus, the surfactant i) is preferably a mixture of molecules with different molecular weights, in other words a statistical distribution of molar weights. Preferably, the second surfactant i) has a molecular weight in the range of 500 to 1200 g / mol. The maximum of the molecular weight distribution curve is preferably between 700 and 900 g / mol, more preferably between 750 and 880 g / mol.

[0041] The second surfactant i) is preferably selected from Propetal 140, Propetal 150, Simulsol DR 301 and Imbentin PPF.

[0042] In surfactant ii), the alkyl group preferably has 8 to 18 carbon atoms, more preferably 10 to 15 carbon atoms. In the surfactant, a mixture of molecules with different alkyl groups may be present. The alkyl group may be one or more branched alkyl groups (if different alkyl groups are present). In another embodiment, the alkyl group mainly consists of one or more branched alkyl groups, which means that small amounts of unbranched alkyl groups may be present. A highly preferred surfactant ii) comprises or consists of isotridecyl polyethylene glycol ether. When surfactant ii) comprises isotridecyl polyethylene glycol ether, said compound is the major compound, i.e. surfactant ii) comprises mainly said compound.

[0043] The polyethylene glycol moiety of surfactant ii) may have a statistical length and weight distribution. Preferably, the polyethylene glycol moiety of surfactant ii) consists of 5 to 22 ethylene glycol units, more preferably 6 to 15 ethylene glycol units. The maximum of the statistical distribution is preferably at 9 to 11 ethylene glycol units. Thus, surfactant ii) may have a mixture of molecules with different lengths of polyethylene glycol moiety. As mentioned above, this can be combined with different alkyl groups. Thus, surfactant ii) may have different alkyl and polyethylene glycol moieties.

[0044] Thus, the surfactant ii) is preferably a mixture of molecules with different molecular weights, in other words a statistical distribution of molar weights. Preferably, the second surfactant ii) has a molecular weight in the range of 400 to 1000 g / mol. The maximum of the molecular weight distribution curve is preferably 650 to 750 g / mol, more preferably 680 to 720 g / mol.

[0045] The second surfactant ii) is preferably selected from Mulsifan RT 203 / 80, Marlipal O13 / 90, Surfaline OX 1006 L, Surfaline OX 1309 L and Genapol UD 079.

[0046] Molecular weights are determined by high performance liquid chromatography coupled with mass spectrometry (HPLC-MS), preferably electrospray ionization time-of-flight (ESI TOF) mass spectrometry.

[0047] The cleaning solution may contain an alkyl glycol ether as a further component. The alkyl glycol ether is not polymeric. Preferred alkyl glycol ethers are ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether or diethylene glycol monobutyl ether. Preferably, the concentration of the alkyl glycol ether in the cleaning solution of the invention is in the range of 100-5000 mg / L, more preferably 500-2000 mg / L. The alkyl glycol ether contributes to the solubilization of the polymeric components and aids in the removal of organic contaminants such as photoresist particles, glove marks or lubricating greases from previous manufacturing steps.

[0048] The cleaning solution may comprise a glycol compound as a further component. The glycol compound is not polymeric. Preferably, the glycol compound is selected from ethylene glycol, propylene glycol, trimethylene glycol and neopentyl glycol.

[0049] The cleaning solution may contain at least one carboxylic acid as a further component, provided that the at least one carboxylic acid is different from the at least one acid already mentioned above. Preferred carboxylic acids are formic acid, acetic acid, citric acid, glycolic acid, tartaric acid, maleic acid or fumaric acid. The at least one carboxylic acid contributes to the removal of organic contaminants such as fingerprints. Preferably, the concentration of the at least one carboxylic acid in the cleaning solution of the invention is in the range of 0.1 to 5% by weight, more preferably 0.2 to 2% by weight. If the cleaning solution contains more than one carboxylic acid, the total concentration of all carboxylic acids is in the range of 0.1 to 10% by weight, more preferably 0.2 to 5% by weight.

[0050] The further components, i.e. alkyl glycol ether, glycol compound, carboxylic acid, may be included in the cleaning solution according to the invention in any combination, i.e. one further component, two or three further components may be included in any combination.

[0051] A further subject of the invention is a method for wetting and / or cleaning a metal surface, comprising a step of treating the metal surface with a cleaning solution as defined above.

[0052] The method is particularly suitable for the treatment of metal surfaces, such as copper, nickel, gold, iron, tin, palladium, ruthenium surfaces or surfaces of alloys of the aforementioned metals, preferably copper or copper alloy surfaces.

[0053] Preferably, the metal surface may be a component of a substrate. The substrate may further comprise a base material, such as a flexible material, such as polyimide, Teflon, ceramic, prepreg or silicon wafer. The substrate may be selected from the group of electrical circuit carriers, such as printed circuit boards (PCBs), copper clad prepregs and chip carriers.

[0054] The treatment can be carried out by any kind of contact of the surface with the cleaning solution, for example by spraying, dipping, immersion, rinsing or by flooding with a submerged sparger nozzle. The preferred technique is dipping. The treatment is preferably carried out at a temperature of 20-70°C, more preferably 30-60°C, even more preferably 35-50°C. The treatment is preferably carried out for a period of 10 seconds to 10 minutes. If only wetting of the surface is desired, the treatment time may be short, for example 10 seconds to 1 minute. If cleaning is desired, a longer treatment time is selected, for example 2-10 minutes, preferably 5-10 minutes.

[0055] As a further step, the method of the present invention can include rinsing the metal surface, preferably with water. Rinsing is performed after treating the metal surface with the cleaning solution of the present invention. Rinsing removes the cleaning solution and contaminants from the metal surface. The advantage of rinsing is that it removes undesirable surfactants that may adversely affect subsequent process steps. Furthermore, the solution can be removed in a short time, thus increasing the overall process speed. The property of the cleaning solution that is removed by rinsing is called rinsability. Thus, the cleaning solution of the present invention has good and fast rinsability.

[0056] When rinsing a metal surface, it remains wet until further process steps are performed, such as applying a further metal layer, applying a separation layer or etching structures such as microvias. This is an additional advantage, since the rinsed surface is better and more uniformly accessible to the chemicals used in the subsequent processing steps, such as the chemicals of the metal deposition bath. Rinsing is preferably performed with excess water and a strong stream in order to efficiently remove the cleaning solution.

[0057] A further subject of the invention is the use of the cleaning solution of the invention for cleaning and / or wetting a metal surface. Cleaning and / or wetting can be carried out by any kind of contact of the surface with the cleaning solution, for example by spraying, dipping, immersion, rinsing or by flooding with a submerged sparger nozzle. The preferred technique is dipping.

[0058] A further subject of the invention is a method for depositing a metal layer on a metal surface, comprising the steps of: (a) providing a metal surface; (b) treating the metal surface with the cleaning solution; (c) treating the metal surface with a metal deposition solution to deposit a metal layer on the metal surface; The method includes:

[0059] Preferably, the metal surface may be a component of the substrate. The substrate may further comprise a base material, such as a flexible material, such as polyimide, Teflon, ceramic, prepreg or silicon wafer. The substrate may be selected from the group of electrical circuit carriers, such as printed circuit boards (PCBs), copper clad prepregs and chip carriers. Preferably, the base material of the PCB or prepreg is made of an epoxy-based material, such as an epoxy blend, such as an epoxy-benzotriazole blend, an epoxy-cyanate blend, an epoxy-propylene blend or an epoxy-polyimide blend, which may optionally be reinforced with a fibrous material, such as glass fiber or woven glass mat.

[0060] The method is particularly suitable for the treatment of metal surfaces, such as copper, nickel, gold, iron, tin, palladium, ruthenium surfaces or surfaces of alloys of the aforementioned metals, preferably copper or copper alloy surfaces.

[0061] The metal of the metal layer is preferably selected from the group comprising tin, gold, silver, palladium, copper, nickel, zinc and ruthenium or alloys thereof, more preferably gold, palladium, copper, nickel or alloys thereof.

[0062] The terms "deposition" and "plating" may be used interchangeably herein.

[0063] The metal deposition solution is preferably aqueous, in other words based on water as a solvent.

[0064] For step (c), several methods are known to those skilled in the art to deposit a metal layer on a metal surface by applying a wet chemical plating method. According to the present invention, the wet chemical plating method is preferably an electroplating method, an electroless plating method or an immersion plating method.

[0065] Electroplating or electrolytic plating is generally described as a plating method using an external current source. Electroless plating is the controlled autocatalytic deposition of a continuous film of metal without the aid of an external supply of electrons. In the present invention, electroless plating should be understood as an autocatalytic deposition using a chemical reducing agent (herein referred to as "reducing agent"). Immersion plating or displacement plating is another deposition of metal without the aid of an external supply of electrons and without the use of a chemical reducing agent. This mechanism relies on the replacement of metal ions present in the immersion plating solution with metal from the substrate to be plated.

[0066] In electroplating or electrolytic plating, the metal deposition solution or liquid contains, in addition to the solvent, water, for example, ions of at least one metal to be deposited, and at least one component that increases the electrical conductivity of the liquid. The liquid may further contain at least one acid / base modifier and / or at least one additive that affects the mechanical, electrical and / or other properties of the metal deposit, and / or affects the thickness distribution of the metal deposit, and / or affects the plating performance of the electroplating liquid, including its stability against degradation, such as oxidation. The ions of the at least one metal may be hydrated ions or complex ions. The acid / base modifier may simply be an acid or base and / or may be a buffering agent. The component that increases the electrical conductivity of the liquid may be a metal salt or an acid or base. The additive may be a brightener, a leveling agent, an antioxidant, a carrier, etc.

[0067] Electroplating can be carried out by using direct, alternating, or pulsed current or voltage.

[0068] Any metal deposition solution may be used for electrodeposition to deposit, for example, copper, nickel, tin, gold, silver, palladium, zinc and ruthenium or alloys thereof. Such electrodeposition solutions are well known to those skilled in the art.

[0069] In a preferred embodiment, the electrodeposition of the copper layer on the metal surface is carried out by known electrodeposition methods and electrolytic copper deposition solutions, such as alkali metal cyanide or non-alkali metal cyanide-based, pyrophosphate complex ion-based or acidic electrolytic copper deposition solutions. Acidic electrolytic copper deposition solutions are preferred. Of these, acidic sulfate and fluoroborate copper deposition solutions are preferred, and acidic sulfate copper deposition solutions are more preferred.

[0070] The copper electrodeposition is preferably performed at 0.1 to 50 A / dm 2 , more preferably 0.5 to 40 A / dm 2 , and even more preferably 1 to 25 A / dm 2 , and even more preferably 1 A / dm 2 ~15A / dm2 In the case where a direct current is applied between the metal surface and the anode, the average current density corresponds to the applied direct current density. In the case where an alternating or pulsed current is applied, the average current density is defined as explained by Chandrasekar et al. (MS Chandrasekar, Malathy Pushpavanam; Pulse and pulse reverse plating - Conceptual advantages and applications; Electrochimica Acta 53 (2008), 3313-3322; Chapter 5). The electrodeposition of copper is preferably carried out at a temperature in the range of 5-80°C, more preferably 10-70°C, even more preferably 15°C-60°C, for a time sufficient to obtain a deposited copper layer of the desired thickness.

[0071] In another preferred embodiment, the electrodeposition of the nickel layer on the metal surface is carried out by known electrodeposition methods and electrolytic nickel deposition solutions such as Watts nickel bath, which is normally used as a bright nickel bath containing nickel sulfate, nickel chloride, boric acid and saccharin as an additive.

[0072] The overall procedure of the electrodeposition method may further include an optional pre-treatment step and an optional post-treatment step. The pre-treatment step may be microetching or pickling. The cleaning solution of the invention is then used (step (b)). The metal surface can then be rinsed with water by one or more rinsing steps and dried, for example air-dried. Then, electrodeposition is carried out (step (c)). The post-treatment step may be washing in water, passivation or drying of the deposited metal layer. Preferably, the metal surface is a component of the substrate.

[0073] An alternative to electrodeposition of metals is their electroless deposition. The main components of an electroless metal deposition solution are a metal salt of the metal to be deposited, a complexing agent, a reducing agent, and optionally an alkaline agent, as well as additives such as stabilizers.

[0074] Any metal deposition solution may be used for electroless deposition to deposit, for example, copper, nickel, tin, gold, silver, palladium, and ruthenium or alloys thereof. Such electroless metal deposition solutions are well known to those skilled in the art.

[0075] In a preferred embodiment, electroless deposition of copper layer on metal surface is carried out by electroless deposition method and electroless copper deposition solution already known in the art.Electroless copper deposition solution typically comprises copper salt, for example copper sulfate or copper hypophosphite; reducing agent, for example formaldehyde, hypophosphite, for example alkali metal salt or ammonium salt, or hypophosphorous acid, or dimethylamine borane; one or more complexing agents, for example tartaric acid, ethylenediaminetetraacetic acid, glycolic acid or triethanolamine; one or more stabilizers, for example oxygen, thiourea, 2-mercaptobenzothiazole, diethyldithiocarbamate or vanadium pentoxide; and pH adjuster, for example sodium hydroxide or potassium hydroxide.Optionally, electroless copper deposition solution comprises brightener and / or wetting agent. Solvent is generally water.

[0076] In another preferred embodiment, the electroless deposition of the nickel layer on the metal surface is carried out by electroless deposition methods and electroless nickel deposition solutions already known in the art.The electroless nickel deposition solution contains a number of substances, including nickel salts, such as nickel sulfate, nickel chloride, nickel acetate or nickel hypophosphite; reducing agents, such as hypophosphites, such as hypophosphites or ammonium salts of alkali metals, such as sodium, sodium borohydride, dimethylamine borane or hydrazine; complexing agents, such as alkylamines, ammonia, carboxylic acids, hydroxyl carboxylic acids, amino carboxylic acids or their salts; stabilizing agents, such as compounds of group VI elements: S, Se, Te, oxygen-containing compounds: AsO2 - , IO3 - , MoO4 2- , Heavy metal cation: Sn 2+ , Pb 2+ , Hg + , Sb 3+or unsaturated organic acids: maleic acid, itaconic acid; and pH adjusters (eg, buffers). Electroless deposition of the nickel layer is usually carried out at relatively high temperatures, ie, in the range of 20°C to 90°C.

[0077] The overall procedure of electroless deposition may further include an optional pre-treatment step and an optional post-treatment step. A metal surface is cleaned with the cleaning solution of the present invention (step (b)). A pre-treatment step such as a desmearing step or an activation step can then be carried out. The metal surface can then be rinsed with water in one or more rinse steps and dried. Then, electroless deposition is carried out (step (c)). Preferably, the metal surface is a component of a substrate.

[0078] In yet another preferred embodiment, the metal deposition is carried out by immersion plating or displacement plating. Typical thicknesses achieved are between 10 and 200 μm.

[0079] Immersion deposition of metal layers onto metal surfaces can be carried out by immersion deposition methods and immersion metal deposition solutions already known in the art. Immersion metal deposition solutions are typically aqueous solutions containing a metal salt of the metal to be deposited, such as a metal cyanide, sulfate, chloride or nitrate; a complexing agent, such as an alkali metal cyanide, ammonium, tartrate, alkali metal thiosulfate or thiourea; and a pH adjuster, such as an alkali metal hydroxide, ammonium, carbonate, sulfuric acid or hydrochloric acid. Any metal deposition solution may be used for immersion deposition, for example to deposit tin, gold, silver and nickel or their alloys. The deposition temperature may vary widely, for example in the range of 10-150° C., depending on the metal to be deposited.

[0080] The general procedure of the immersion deposition method may further include an optional pre-treatment step and an optional post-treatment step. The pre-treatment step may be pickling the metal surface, washing in water, and polishing to a bright finish. The cleaning solution of the present invention is then used (step (b)). The metal surface is then washed and can be dipped in a cyanide or acid solution, depending on whether the immersion deposition solution used later is alkaline cyanide or acidic. Immersion deposition is then performed (step (c)). The post-treatment step may be washing in water and drying the deposited metal layer. Preferably, the metal surface is a component of the substrate.

[0081] Treatment of the metal surface with the cleaning solution of the present invention improves the adhesion of the deposited metal layer to the metal surface. This is shown in FIG. 5. FIG. 5 shows a cross section of a portion of a through hole present in a multilayer PCB. The multilayer PCB comprises at least three layers of base material (2) and at least two layers of copper circuit lines, each layer of copper circuit lines being present between two layers of base material. These layers of copper circuit lines are called copper inner layers (4). The base material (2) is reinforced with glass fibers. The outer surface of the outer layer of the base material may be copper foil clad (not shown in FIG. 5). The through hole passes through these layers. A stack of electrolessly deposited copper layers and electrodeposited copper layers (3) is deposited on the wall of the through hole. An electrolessly deposited copper layer is applied directly on the wall of the through hole, and an electrolytically deposited copper layer is plated on the electroless copper layer. The remaining space in the through hole is filled with solder (1). Prior to depositing the electrodeposited copper layer, the surface of the electrolessly deposited copper layer was cleaned with the cleaning solution of the present invention, as described in Example 2.4 herein. After depositing the electrodeposited copper layer, the solder (1) penetrated into the through-hole during the solder shock test described in the same Example 2.4. The contact area between the copper inner layer (4) and the stack of deposited copper layers (3) is referred to as the interconnect or interconnection. Figure 5 shows that no defects such as peeling or voids occurred in the interconnect or contact area between the electrolessly deposited copper layer and the electrodeposited copper layer during the solder shock test. This means that the cleaning method and cleaning process of the metal deposition method of the present invention have excellent cleaning and wettability as well as excellent rinsability.

[0082] The method of depositing a metal layer on a metal surface according to the present invention comprises the steps of: (d) the further step of bonding the metal surface to a resist material and imaging the resist material. may include:

[0083] A further method step (d) may be performed between method steps (b) and (c), or after method step (c), or between method steps (b) and (c) and after method step (c). Method steps (b), (c) and (d) may be repeated, or method steps (b) and (c) may be repeated.

[0084] Treatment of metal surfaces with the cleaning solutions of the present invention also improves the adhesion of resist materials to the metal surfaces.

[0085] The resist material may be a photoimageable resist or a solder resist.

[0086] Methods for producing metal surfaces, for example copper-clad printed circuit board materials, for subsequent coating of said metal surfaces with a resist material are known in the art. At various stages in the process of producing printed circuit boards, metal surfaces, for example copper surfaces, of printed circuit board materials are coated with a resist, which must adhere to the metal surfaces. For example, in the production of metal structures, i.e. copper lines and soldering of bonding and pads, photoimageable resists are used to define these structures. Furthermore, after these metal structures are produced, solder masks are applied to these structures in areas where soldering is not to be performed. In both cases, a resist is applied to the metal surface, which must adhere sufficiently to it during the imaging process (exposure and development) and during any subsequent process steps, such as plating or soldering of further metal layers, such as copper (in the course of producing copper structures). Imaging processes of resist materials are known in the art. For this reason, cleaning of the metal surface should be performed in any case, for example, to give the metal surface a good resist receptivity and therefore adhesion to said metal surface.

[0087] In a preferred embodiment, the photoimageable resist, also called plating or etching resist, is usually an acrylic resist, i.e. it has an acrylic or methacrylic backbone. These resists are usually applied to the metal surface as a dry or liquid film.

[0088] In another preferred embodiment, the solder resist, also called solder mask or solder stop mask, is a polymer layer. The polymer for the solder mask is epoxy resin based.

[0089] Solder masks can be bonded to metal surfaces in a variety of ways. Solder masks can be applied as a liquid, which is silk screened onto the metal surface. Other types are photoimageable liquid solder mask (LPSM) inks and dry film photoimageable solder mask (DFSM). The LPSM can be silk screened or sprayed onto the circuit carrier, exposed and developed to provide openings for the conductive line patterns of the components to be soldered to the metal pads. The DFSM is vacuum laminated onto the metal surface, then exposed and developed. The polymer layer of the solder mask is then thermally cured.

[0090] The solder mask must withstand soldering conditions, such as high temperatures, and remains on the metal surface of the circuit carrier after the manufacturing process throughout the life of the circuit carrier.

[0091] example The invention will now be further illustrated by examples.

[0092] 1. Materials and Methods 1.1 Surfactants As so-called first surfactants the following surfactants were used throughout the examples:

[0093] Propetal 120 and Propetal 105 are products and trademarks of Zschimmer and Schwarz, Lahnstein, Germany. Propetal 120 and Propetal 105 (CAS 154518-36-2 or 155683-77-5) are ethoxylated / propoxylated fatty alcohols.

[0094] Antarox B12DF is a product and trademark of Solvay Solutions Nederland BV (CAS 37311-00-5). Antarox B12DF is an ethoxylated / propoxylated dodecanol. Antarox B12DF is abbreviated below as Antarox.

[0095] Marlox MO 154 is a product and trademark of Sasol Germany GmbH (CAS 68439-51-0). Marlox MO 154 is an ethoxylated / propoxylated alcohol, the alcohol moiety having 12-14 carbon atoms. Marlox MO 154 is hereinafter abbreviated as Marlox.

[0096] As so-called second surfactant options i), the following surfactants were used throughout the examples:

[0097] Propetal 140 and Propetal 150 (CAS 154518-36-2) are products and trademarks of Zschimmer and Schwarz. Propetal 140 and Propetal 150 are ethoxylated / propoxylated fatty alcohols.

[0098] Simulsol DR 301 (CAS 68154-97-2) is a product and trademark of Seppic, Cologne, Germany. Simulsol DR 301 is hereinafter abbreviated as Simulsol 301. Simulsol 301 is an ethoxylated / propoxylated fatty alcohol, which has 10 to 12 carbon atoms (C 10 ~C12 alcohol).

[0099] Imbentin PPF is a product and trademark of Kolb GmbH, Hedingen, Switzerland. Imbentin PPF is hereinafter abbreviated as "Imbentin". Imbentin is an ethoxylated / propoxylated C8-C 18 It is an alcohol. Its CAS number is 69013-18-9.

[0100] As so-called second surfactant option ii) the following surfactants were used throughout the examples:

[0101] Mulsifan RT 203 / 80 is a product and trademark of Zschimmer & Schwarz. Mulsifan RT 203 / 80 is hereinafter abbreviated as Mulsifan. Mulsifan is an ethoxylated C 12 ~C 15 It is a fatty alcohol.

[0102] Marlipal O13 / 90 (CAS 69011-36-5) is a product and trademark of Sasol Germany GmbH, Hamburg, Germany. Marlipal O13 / 90 is abbreviated below as Marlipal. Marlipal is an ethoxylated isotridecanol with 5 to 20 ethylene glycol units.

[0103] Surfaline OX 1006 L (CAS 61827-42-7) and Surfaline OX 1309 L (CAS 9043-30-5) are products and trademarks of CECA SA (France). Surfaline OX 1006 L is hereinafter abbreviated as "Surfaline 1006". Surfaline 1006 is an ethoxylated C 2 -butyl 1,2 -dimethyl 2 -phenyl ether with 6 ethylene glycol units. 10It is a fatty alcohol. Surfaline OX 1309 L is hereinafter abbreviated as "Surfaline 1309". Surfaline 1309 is an ethoxylated isotridecanol with 9 ethylene glycol units.

[0104] Genapol UD 079 is a product and trademark of Clariant Corporation, North Carolina, USA. Genapol UD 079 is hereinafter abbreviated as Genapol. Genapol is an ethoxylated undecanol.

[0105] 1.2 Cleaning solutions A cleaning solution was prepared using the following ingredients:

[0106] - Sulfuric acid: 10% by weight optionally, one or more carboxylic acids - Ethylene glycol monobutyl ether: 1000 mg / l unless otherwise stated - 1 or 2 surfactants - The balance is water.

[0107] The type and concentration of surfactants, and the type and concentration of carboxylic acids, when used in a particular example, are indicated in the description of the example. When concentrations are given in ppm, this is equivalent to mg / l.

[0108] 1.3 Cloud point measurement Cloud points were determined according to the German version of European Standard EN 1890:2006, section 8.2, procedure A, with the following modifications: 10% by weight H2SO4 was used as the solvent and the surfactant concentration was 1000 mg / L. When surfactant mixtures were measured, the surfactant concentration may differ from 1000 mg / L. The concentrations of the surfactants used in the mixtures are indicated in the description of the specific examples.

[0109] 100ml of the dissolved surfactant was filled into a beaker and slowly heated on a magnetic stirrer. After the solution became cloudy, the heater was switched off. The solution was slowly cooled while monitoring the temperature of the surfactant solution. The cloud point was reached when the solution became clear again, and the temperature of this cloud point was recorded.

[0110] 1.4 Measurement of static surface tension The static surface tension is measured using the Wilhelmy plate method, which uses a platinum thin plate of a given size to measure the interfacial tension at the gas-liquid interface. To do this, the plate is immersed in a solution to a given depth and then pulled out of the solution while measuring the force required to pull it out. This force is correlated with the static surface tension.

[0111] 1.5 Measurement of dynamic surface tension The surface tension related to surface life is called dynamic surface tension. For liquids containing surface-active substances (surfactants), the dynamic surface tension may differ from the surface tension at equilibrium. Immediately after a surface is created, the dynamic surface tension of a surfactant solution in contact with this new surface has the same value as the pure liquid. As the surface ages, i.e., in prolonged contact with the surfactant, the surface tension decreases due to the adsorption of the surfactant at the surface until equilibrium is reached. The time required to reach equilibrium depends on the diffusion and adsorption rates of the surfactant. The lower the surface tension, the better the wetting and cleaning properties. Therefore, dynamic surface tension is a good indicator of the extent and speed of wetting and cleaning.

[0112] Dynamic surface tension was measured with a bubble pressure tensiometer. The surface tension of a surface in the process of forming, i.e. a bubble surface, is measured. The tensiometer generates bubbles in a solution of the surfactant to be tested. The size and lifetime of the interface of the bubble and the surfactant solution change during the measurement. During foaming, the bubble pressure reaches a maximum value, which is recorded by the tensiometer. The time from the start of foaming to the maximum pressure is called the surface lifetime. The surface tension is measured as a function of the surface lifetime.

[0113] The measurements were carried out as follows.

[0114] - Kruess (Hamburg, Germany) Foam Pressure Tensiometer BP2 - Temperature 23℃ - The surfactants were solubilized in 10% by weight H2SO4 in water. The concentrations of the surfactants are given in the examples or as above.

[0115] 1.6 Measurement of cleaning performance The cleaning performance of various cleaners was tested by applying three fingerprints of different people to a panel of standard copper-clad base material as a sample. After cleaning, the panel was plated with copper.

[0116] Test procedure: 1. Three different fingerprints were applied to the copper clad material.

[0117] 2. The fingerprinted sample was cleaned using the cleaning solutions of the present invention and the comparative example at 35° C. for 3 minutes while stirring the solutions slowly with a magnetic stirrer.

[0118] 3. The samples were rinsed with tap water for 2 minutes.

[0119] 4. The samples were treated with an acid pre-dip (5 wt % H2SO4) for 1 min.

[0120] 5. The sample was electrochemically coated with 1.5 A / dm in an acid copper electrochemical bath (Cupracid TP, product of Atotech Deutschland GmbH). 2 The copper was plated at 0.5° C. for 30 minutes.

[0121] 6. Cleaning performance was graded by visual inspection.

[0122] Grading was done by judging the fingerprint after plating on a scale of 1 to 5. "5" is the best result, representing maximum cleaning effectiveness with only a small visible fingerprint remaining, and "1" is the worst cleaning performance, with the fingerprint still clearly visible. The fingerprint is completely present. No initial weakening or rinsing loss of the fingerprint can be detected.

[0123] 1.7 ICD Testing ICD testing (ICD=Interconnection Defect) is usually performed as a quality control of the strength of copper layers deposited on polymeric materials, i.e., printed circuit boards (PCBs) and interconnects. In this document, the metallization of metal surfaces, the quality of cleaning and the quality of rinsing are tested using ICD testing. The main step of ICD testing is the solder shock test. The solder shock process is used to test whether the adhesion of the electrolytically plated copper layer is sufficient on the already existing copper layer (electrolessly deposited) and on the exposed parts of the already existing copper inner layer. The contact area of ​​the stack of electrolytically plated and electrolessly deposited copper layers and the exposed parts of the copper inner layer is called the interconnect. The solder shock process is performed after cleaning the already existing electroless copper layer and the exposed parts of the copper inner layer with a cleaning solution. If the cleaning is insufficient and organic contaminants are still present on the exposed parts of the electroless copper layer and the copper inner layer after cleaning, the adhesion of the electrolytically plated copper layer will be poor and defects such as delamination and voids will occur due to the solder shock process. If the rinsing after cleaning is insufficient and surfactant residues from the cleaning solution are still present on the exposed portions of the electroless copper layer and inner copper layer, the adhesion of the electrolytically plated copper layer will also be compromised and similar defects will occur during the solder shock process. If defects occurred during the solder shock process, the tested cleaning solution failed the ICD test.

[0124] The ICD test is therefore an indication of the quality of cleaning and wetting of pre-existing metal layers with the cleaning solution of the present invention as well as the rinsability of said cleaning solution. Metal layers deposited on the walls of through-holes in such substrates are particularly sensitive to the solder shock test, which is a thermal stress test. Samples of metal layers deposited on polymer substrates were floated (repeatedly) on hot solder and then examined by microsection analysis. The mismatch in thermal expansion coefficients of the polymer substrate and the metal leads to high mechanical stresses that may cause damage to metal-plated polymer substrates. This procedure is a modified version of the IPC standard IPC-TM-650, Number 2.6.8, Revision E, Thermal Stress, Plated-Through Holes.

[0125] Typical defects are corner cracks, barrel cracks, inner layer interconnect separation, resin recession, pull out, pad rotation, pad lift, delamination, resin cracks and extreme deformation of the specimen. If the specimen shows no such defects after application of the solder shock test, the cleaning and / or wetting of the metal layer already present on the substrate and the rinsability of the cleaning solution were of the highest quality.

[0126] Sample preparation Standard copper-clad base material with through-holes (multi-layer substrate with two copper inner layers and copper cladding on both outer surfaces) was used as the samples. These samples had already been de-smeared and electrolessly plated with a 1 μm thick copper layer on the copper cladding and on the walls of the through-holes.

[0127] The samples were washed with the cleaning solution of the present invention and the comparative cleaning solution at 35° C. for 5 minutes with slow solution stirring using a magnetic stirrer. The cleaning solutions are outlined below. The samples were then rinsed with tap water for 1 minute and deionized water for 5 seconds. The samples were air-dried at room temperature (approximately 21° C.) for 2 hours. They were then washed with an acid copper electrodeposition bath (Cupracid BL R, product of Atotech Deutschland GmbH, DC 1.5 A / dm 2The samples were copper plated using a 2000 cc 10000 sintered copper bath (1000 sintered copper, 136 min, room temperature). The resulting copper layer was 45 μm thick.

[0128] Both openings of the through-holes metallized in this procedure were then covered with adhesive tape to simulate an etch resist (to protect the copper in the holes during the etching process). The parts of the copper layer on the substrate that were not covered by the tape and remained intact were then removed by etching with a HNO3 solution (concentrated HNO3:water:1=1). The tape was then removed from the sample and the adhesive residue resulting from the tape was removed from the sample with an organic solvent. Finally, the sample was annealed at 140°C for 6 hours to reduce the stress of the electrodeposited copper layer. The sample was allowed to cool to room temperature before solder shock testing.

[0129] Solder Impact Test The electroplated specimens were immersed in flux to completely remove the oxide layer from the copper surface and to allow excess flux to drain off. The specimens were floated in a warm solder bath for at least 10 seconds. The specimens were then removed from the solder and allowed to cool for at least 10 minutes. The specimens were shocked using the procedure outlined above as follows: Specimen 1 was shocked 6 times at 288°C; Specimen 2 was shocked 9 times at 288°C; Specimen 3 was shocked 6 times at 326°C. Finally, the specimens were thoroughly rinsed with isopropanol to remove excess flux residue. The specimens were then dried using airflow.

[0130] Microsection preparation The samples were cut into single strips such that the through-holes were cut through their centers. The samples were embedded in epoxy resin, and the resulting blocks of resin-embedded samples were ground and polished until a cross section through the center of the through-holes was clearly visible. The samples were examined under an optical microscope to detect such defects. Some samples were further examined under a scanning electron microscope (SEM).

[0131] 2. Working Example 2.1 Cloud point and static surface tension Solutions of surfactants were prepared and their cloud points and static surface tensions were measured as described in Sections 1.3 and 1.4. Unless otherwise stated, the concentration of each surfactant was 1000 ppm surfactant in 10 wt% H2SO4 in the prepared solutions. The results are summarized in Table 1.

[0132] [Table 1]

[0133] The cloud point of Propetal 120 increased when mixed with Simulsol 301, Marlipal or Mulsifan. The static surface tension of the mixtures is in a similar range compared to the performance of the single surfactants.

[0134] 2.2 Dynamic surface tension The synergistic effect was quantified in surfactant mixtures with respect to dynamic surface tension.

[0135] For quantification of the synergistic effect, the surface tension of the surfactant mixture (dynamic measurement) at different surface lifetimes was assumed to be proportional to the surface tension of the surfactant alone. The surface lifetime chosen was 100 ms, since rapid wetting of the surface is essential for applications such as cleaning of blind microvias (vertical interconnect access).

[0136] Each surfactant used was designated A and B, and B was assumed to have a lower surface tension than the given surface lifetime. When used as the sole surfactant in solution, the concentration was c A =c total and c B =c total The surface tension of a single surfactant is σ A and σ B It is.

[0137] The difference in surface tension is Δ A,B = σ A-σ B When a mixture of surfactant A and surfactant B is used in solution, the total concentration of each surfactant is c A +c B =c total It is.

[0138] Next, c in the mixture of A and B A +c B =c total Theoretical surface tension σ theor teeth, [ka] It is.

[0139] For the calculation of the synergistic effect, the actually obtained value of the surface tension of the mixture σ A,B and the predicted theoretical surface tension of the mixture as a function of the difference in the surface tension of the individual surfactants: [ka]

[0140] If the result is positive, the surface tension of the mixture is lower than expected and the rate of wetting and cleaning is higher. The lower the surface tension, the better the wetting and cleaning. If the result is negative, the surface tension of the mixture is higher than expected.

[0141] Dynamic surface tension was measured as described in Section 1.5. Unless otherwise stated, the dynamic surface tension was measured at a concentration of c for single surfactant A or B when a single surfactant was used in solution. A or c B was 1000 ppm for each surfactant used in the dynamic surface tension measurements. Unless otherwise stated, when a mixture of surfactant A and surfactant B was used in solution, the concentration of each individual surfactant A or B, c A or c B is 500 ppm, and the total surfactant concentration c total was 1000 ppm.

[0142] 2.2.1 Dynamic Surface Tension of Propetal 120 and Propetal 150 Figure 1 shows the dynamic surface tension (σ) of a mixture of Propetal 120 (surfactant A) and Propetal 150 (surfactant B) compared to the individual surfactants. The data is summarized in Table 2. ("Surface Life" in Figure 1 corresponds to "Foam Life" in Table 2.) Calculations using the above formula at 100 ms surface tension values ​​produced the results summarized in Table 3.

[0143] [Table 2]

[0144] [Table 3]

[0145] 2.2.2 Dynamic surface tension of Propetal 120 and Marlipal Dynamic surface tension data for mixtures of Marlipal (Surfactant A) and Propetal 120 (Surfactant B) compared to the individual surfactants is summarized in Table 4. Calculations using the above formula at 100 ms surface tension values ​​produced the results summarized in Table 5.

[0146] [Table 4]

[0147] [Table 5]

[0148] 2.2.3 Dynamic Surface Tension of Propetal 120 and Simulsol 301 Dynamic surface tension data for mixtures of Simulsol 301 (Surfactant A) and Propetal 120 (Surfactant B) compared to the individual surfactants is summarized in Table 6. Calculations using the above formula at 100 ms surface tension values ​​produced the results summarized in Table 7.

[0149] [Table 6]

[0150] [Table 7]

[0151] 2.2.4 Dynamic Surface Tension of Propetal 120 and Mulsifan Dynamic surface tension data for mixtures of Mulsifan (Surfactant A) and Propetal 120 (Surfactant B) compared to the individual surfactants is summarized in Table 8. Calculations using the above formula at 100 ms surface tension values ​​produced the results summarized in Table 9.

[0152] [Table 8]

[0153] [Table 9]

[0154] 2.2.5 Dynamic Surface Tension of Propetal 120 and Propetal 140 The dynamic surface tension (σ) of a mixture of Propetal 120 (surfactant A) and Propetal 140 (surfactant B) compared to the individual surfactants is shown in Figure 2. The dynamic surface tension data is summarized in Table 10. ("Surface Life" in Figure 2 corresponds to "Foam Life" in Table 10.) Calculations using the above formula at 100 ms surface tension values ​​produced the results summarized in Table 11.

[0155] [Table 10]

[0156] [Table 11]

[0157] The above results of Examples 2.2.1-2.2.5 demonstrate the synergistic effect of the surfactant mixtures used in the cleaning solutions of the present invention, which have lower dynamic surface tensions and higher wetting rates than the single surfactants.

[0158] 2.2.6 Dynamic Surface Tension of Propetal 105 and Simulsol 301 Dynamic surface tension data for mixtures of Propetal 105 (Surfactant B) and Simulsol 301 (Surfactant A) compared to the individual surfactants is summarized in Table 12. The concentration of Propetal 105 in the mixture was 500 ppm and the concentration of Simulsol 301 in the mixture was 1500 ppm. Surfactant solutions containing only a single surfactant each had a surfactant concentration of 2000 ppm. Calculations using the above formula at 100 ms surface tension values ​​produced the results summarized in Table 13.

[0159] [Table 12]

[0160] [Table 13]

[0161] 2.2.7 Dynamic Surface Tension of Propetal 105 and Propetal 150 Dynamic surface tension data for mixtures of Propetal 105 (Surfactant B) and Propetal 150 (Surfactant A) compared to the individual surfactants is summarized in Table 14. Calculations using the above formula at 100 ms surface tension values ​​produced the results summarized in Table 15.

[0162] [Table 14]

[0163] [Table 15]

[0164] 2.2.8 Dynamic Surface Tension of Propetal 105 and Marlipal Dynamic surface tension data for mixtures of Propetal 105 (Surfactant B) and Marlipal (Surfactant A) compared to the individual surfactants is summarized in Table 16. Calculations using the above formula at 100 ms surface tension values ​​produced the results summarized in Table 17.

[0165] [Table 16]

[0166] [Table 17]

[0167] The above results of Examples 2.2.6 to 2.2.8 show the synergistic effect of the surfactant mixtures used in the cleaning solutions of the present invention, which have lower dynamic surface tensions and higher wetting rates than the single surfactants.

[0168] The following examples are comparative examples and demonstrate the lack of synergy: in these cases, synergy is a negative value.

[0169] 2.2.9 Dynamic Surface Tension of Surfaline 1309 and Surfaline 1006 Table 18 shows the dynamic surface tension of mixtures of Surfaline 1309 (Surfactant A) and Surfaline OX 1006 L (Surfactant B). Calculations using the above formula at 100 ms surface tension values ​​gave the results summarized in Table 19.

[0170] [Table 18]

[0171] [Table 19]

[0172] 2.2.10 Dynamic Surface Tension of Surfaline 1309 and Simulsol 301 The dynamic surface tension (σ) of mixtures of Simulsol 301 (surfactant A) and Surfaline 1309 (surfactant B) is shown in Figure 3. The dynamic surface tension data is shown in Table 20. ("Surface Life" in Figure 3 corresponds to "Bubble Life" in Table 20.) Calculations using the above formula at 100 ms surface tension values ​​produced the results summarized in Table 21.

[0173] [Table 20]

[0174] [Table 21]

[0175] 2.2.11 Dynamic Surface Tension of Simulsol 301 and Imbedin Table 22 shows the dynamic surface tension of mixtures of Simulsol 301 (Surfactant A) and Imbentin (Surfactant B). Calculations using the above formula at 100 ms surface tension values ​​yielded the results summarized in Table 23.

[0176] [Table 22]

[0177] [Table 23]

[0178] 2.2.12 Dynamic Surface Tension of Propetal 150 and Propetal 140 Table 24 shows the dynamic surface tension of mixtures of Propetal 150 (Surfactant A) and Propetal 140 (Surfactant B). Calculations using the above formula at 100 ms surface tension values ​​yielded the results summarized in Table 25.

[0179] [Table 24]

[0180] [Table 25]

[0181] 2.2.13 Dynamic Surface Tension of Antarox and Propetal 105 Table 26 shows the dynamic surface tension of mixtures of Antarox (Surfactant A) and Propetal 105 (Surfactant B). Calculations using the above formula at 100 ms surface tension values ​​yielded the results summarized in Table 27.

[0182] [Table 26]

[0183] [Table 27]

[0184] 2.2.14 Dynamic Surface Tension of Propetal 120 and Propetal 105 Table 28 shows the dynamic surface tension of mixtures of Propetal 120 (Surfactant A) and Propetal 105 (Surfactant B). Calculations using the above formula at 100 ms surface tension values ​​yielded the results summarized in Table 29.

[0185] [Table 28]

[0186] [Table 29]

[0187] 2.3 Cleaning metal surfaces Samples of metal surfaces as described in section 1.6 were cleaned with a cleaning solution according to the invention and two comparative cleaning solutions. One cleaning solution according to the invention (inventive example 1 in FIG. 4) contained a mixture of Marlox (first surfactant, 1000 ppm) and Surfaline 1309 L (second surfactant ii), 2550 ppm). The further components of the cleaning solution according to the invention and their concentrations in the cleaning solution were as outlined herein in section 1.2, with the exception of ethylene glycol monobutyl ether, which was not included in this cleaning solution. Another cleaning solution according to the invention (inventive example 2 in FIG. 4) contained a mixture of Propetal 105 (first surfactant, 500 ppm) and Genapol UD 079 (second surfactant ii), 1500 ppm). This cleaning solution further contained glycolic acid (carboxylic acid) at a concentration of 0.48 wt. % and ethylene glycol monobutyl ether at a concentration of 0.1 wt. %. One comparative cleaning solution (Comparative Example 1 in FIG. 4) contained the surfactant Tegotens EC 11 (Evonik Industries AG; CAS number 67922-59-2; fatty alcohol ethoxylate endcapped with butylene oxide; 350 ppm) and no further surfactant. This comparative cleaning solution further contained about 10 wt. % sulfuric acid, about 0.5 wt. % hydroxyacetic acid, and about 0.075 wt. % diethylene glycol monobutyl ether. Another comparative cleaning solution (Comparative Example 2 in FIG. 4) contained two surfactants, namely 700 ppm Amonyl 265 BA (Seppic GmbH; CAS number 68424-94-2; cocoalkyl dimethyl betaine, amphoteric surfactant) and 1000 ppm Marlox. This comparative cleaning solution further contained about 10 wt. % sulfuric acid, about 0.48 wt. % hydroxyacetic acid, and about 0.1 wt. % ethylene glycol monobutyl ether. The cleaning results are shown in FIG. 4. The best cleaning results (rank 4) were obtained with the cleaning solution of the invention. On the samples washed with the solution of the invention, no or almost no fingerprints were visible anymore. The samples are completely washed. In contrast, the samples treated with the comparative cleaning solution clearly show fingerprints.

[0188] 2.4 Cleaning, Rinsing and Metallization The quality of cleaning, the quality of rinsing until surfactant residues were removed, and the quality of metallization were determined by ICD testing.

[0189] For void-free production (e.g. for blind microvia filling), it is very important that no contaminants or residues of cleaning agent components remain on the copper surface after cleaning and rinsing. Surfactants in particular can adhere to the copper surface by adsorption and block the surface. This leads to an effect similar to passivation, which can lead to voids during copper plating. To check whether the cleaning agents have good cleaning properties and can be easily rinsed, ICD tests were performed as described in section 1.7 on samples that were cleaned with different cleaning agents and then metallized. One sample was cleaned with a cleaning solution according to the invention containing a mixture of Propetal 105 (first surfactant, 500 ppm) and Genapol UD 079 (second surfactant ii, 1500 ppm). This cleaning solution further contained glycolic acid (carboxylic acid) at a concentration of 0.48 wt. % and ethylene glycol monobutyl ether at a concentration of 0.1 wt. %. Another sample was cleaned with the comparative cleaning solution also used in comparative example 1 (Figure 4) in section 2.3. Unremoved contaminants and adsorbed surfactants reduce the adhesion between the electrodeposited copper layer and the cleaned electrolessly deposited copper surface, especially in the through-holes, thereby causing defects as described in Section 1.7. ICD testing was performed as described in Section 1.7.

[0190] Figure 5 shows a cross-section of a through-hole obtained from a sample cleaned with the cleaning solution of the present invention. After six solder shocks at 326°C, a void-free interlayer connection is obtained. The electrodeposited copper layer did not peel off from the cleaned and electrolessly deposited underlying copper layer. The adhesion obtained between the electrodeposited copper layer and the electrolessly deposited copper layer after treating the electrolessly deposited copper surface with the cleaning solution of the present invention is excellent.

[0191] The results of the ICD test are summarized in Table 30. The comparative example shows the results when a comparative cleaning solution containing only one surfactant was used. The results are expressed as the number of defects found per 100 in the interconnect area of ​​the samples inspected (ICD / 100 inner layers). The fewer defects a sample had, the better the cleaning and rinsability. The best results were obtained with samples treated with the cleaning solution of the present invention.

[0192] [Table 30]

Claims

1. 1. A cleaning solution for cleaning a metal surface, said cleaning solution comprising: at least one acid which is sulfuric acid, a first surfactant which is an alkyl poly(ethylene glycol-co-propylene glycol) ether having a cloud point of ≦25° C., the alkyl group having 8 to 15 carbon atoms; and - ii) a second surfactant selected from alkyl polyethylene glycol ethers having a cloud point of ≥ 45°C and the polyethylene glycol moiety consists of 6 to 15 ethylene glycol units; Including, Here, the cloud point is determined according to the German version of the European standard EN 1890:2006, section 8.2, procedure A, using 10% by weight H as solvent. 2 SO 4 and a surfactant concentration of 1000 mg / L, the concentration of the at least one acid in the cleaning solution is between 5 and 30% by weight; the concentration of the first surfactant in the cleaning solution is 50 to 5000 mg / L; The concentration of the second surfactant in the cleaning solution is 50 to 20,000 mg / L. Cleaning solution.

2. 2. The cleaning solution of claim 1, wherein the weight ratio of the first surfactant to the second surfactant is in the range of 1:0.5 to 1:

10.

3. 3. The cleaning solution of claim 1 or 2, wherein the first surfactant may comprise a mixture of molecules having different alkyl groups.

4. 4. A cleaning solution according to claim 1, wherein in the second surfactant ii) the alkyl group comprises one or more branched alkyl groups.

5. 5. The cleaning solution of claim 1 further comprising an alkyl glycol ether.

6. A method for cleaning a metal surface, comprising treating the metal surface with a cleaning solution according to any one of claims 1 to 5.

7. 6. Use of a cleaning solution according to any one of claims 1 to 5 for cleaning metal surfaces.

8. 1. A method for depositing a metal layer on a metal surface, comprising the steps of: (a) providing a metal surface; (b) treating the metal surface with a cleaning solution according to any one of claims 1 to 5; (c) treating the metal surface with a metal deposition solution to deposit the metal layer on the metal surface; A method comprising:

Citation Information

Patent Citations

  • Water-based detergent

    JP1996104890A

  • Cleaning water solution for aluminum based metal and cleaning method thereof

    JP2000104185A

  • Liquid detergent having good oil-separation and penetration properties

    JP2000336391A

  • Low foaming automatic dishwashing composition

    JP2002502445A

  • Liquid detergent composition for automatic dishwasher

    JP2003277800A